Korelasi Antara Karakteristik dengan Tingkat Pengetahuan Early Warning Score Perawat di Ruang Rawat Inap (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2023)
Background: The Early Warning Score (EWS) is a tool for assessing changes in a patient's condition and is a hospital-certified metric. The use of EWS in Indonesia is still low, one of the factors being the nurse's knowledge of EWS. The purpose of this study is to clarify the relationship between EWS characteristics and knowledge levels of inpatient nurses, mostly in intensive care units and emergency care units. The novelty of this study is also related to the characteristics of the caregiver.Methods: The survey method was quantitative, using a descriptive correlation approach. The population was all nurses in the hospital room. Sampling techniques included target sampling by specified criteria of 27 people. The data was collected cross-sectional using demographic and knowledge questionnaires.Results: almost all respondents (77.8%) were in early adulthood; some were registered nurses; and almost all (85.20%) of respondents had more than 3 years of work experience. Respondents (40.7%) completed the apprenticeship, and almost half (48.1%) of the respondents had sufficient knowledge. There was no correlation between age (p-value 0.423), education (p-value 0.308), work experience (p-value 0.990), EWS monitoring training and socialization (p-value 0.716), and level of knowledge about EWS because the p-value was 0.05.Conclusion: There was no relationship between age, education, work experience, and training and the level of knowledge of nurses about EWS. More samples can be used to investigate and search for the most dominant factors that influence knowledge.